2021
DOI: 10.1111/ene.15091
|View full text |Cite
|
Sign up to set email alerts
|

RNF170 mutation causes autosomal dominant sensory ataxia with variable pyramidal involvement

Abstract: Background Although hereditary ataxias are a group of clinically and genetically heterogeneous disorders, specific clinical clues can sometimes incriminate certain genes. This can trigger genetic testing in sporadic patients or prompt dissecting certain genes more thoroughly when initial genetic testing is negative. Also for the assembly of gene panels and interpretation of the results, genotype−phenotype correlations remain important to establish. Methods We clinically evaluated a Belgian family with autosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The heterozygous mutation c.595C>T (p.R199C) within RNF170 was formerly shown to induce autosomal dominant sensory ataxia (ADSA) in four unrelated lines from Canada, Ecuador, and Belgium through toxic gain‐of‐function. Patients always present with late‐onset proprioceptive loss and progressive ataxia with ubiquitinated protein aggregates in brain tissue 9–11 . The first four RNF170 ‐related AR‐HSP families were reported in 2019, and cellular and zebrafish studies revealed LoF as the pathogenic mechanism of those homozygous variations 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterozygous mutation c.595C>T (p.R199C) within RNF170 was formerly shown to induce autosomal dominant sensory ataxia (ADSA) in four unrelated lines from Canada, Ecuador, and Belgium through toxic gain‐of‐function. Patients always present with late‐onset proprioceptive loss and progressive ataxia with ubiquitinated protein aggregates in brain tissue 9–11 . The first four RNF170 ‐related AR‐HSP families were reported in 2019, and cellular and zebrafish studies revealed LoF as the pathogenic mechanism of those homozygous variations 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients always present with lateonset proprioceptive loss and progressive ataxia with ubiquitinated protein aggregates in brain tissue. [9][10][11] The first four RNF170-related AR-HSP families were reported in 2019, and cellular and zebrafish studies revealed LoF as the pathogenic mechanism of those homozygous variations. 4 Since then, two more mutations have been found.…”
Section: Discussionmentioning
confidence: 99%